Prevalence and Genotypic Distribution of Hepatitis C Virus in Peshawar KPK, Pakistan - Nazir Ahmad; Mian Khizar Hayat; Bo-Xuan Gao; Shah Faisal; Nikhat Ilahi; Barkat Ali; Sahib Zada; Tanweer Kumar; Wasim Sajjad (HAYATI Journal of Biosciences, 2017)
This present study was planned to obtain an up-to-date picture of Hepatitis C virus (HCV) infection and its genotypes distribution in Peshawar, Khyber Pakhtunkhwa, Pakistan, as well as of the relationship between HCV genotypes and demographic and clinical parameters, and the risk factors in patients with an HCV subtype. Samples (blood) from 1978 individuals were collected and were tested using a strip-based method called the immunochromatographic test (ICT) for the existence of antibodies against HCV. It was observed that 158 of the 1978 individuals (7.9%) harbored antibodies in their blood against HCV, among which the female percentage (53.2%) was higher than that of the male (46.8%). Among the different age groups, the highest number of incidences of HCV antibodies was found in the age group of 31–40 years (26.6%). ICT positive samples were further screened by polymerase chain reaction (PCR) to determine the existence of active HCV-RNA, and it was found that 6.21% (123) of the total population (1978) tested, was positive, among which the female rate (56.91%) was observed to be higher than that of the male (43.09%). The highest incidence recorded was in the age group of 41–50 years (33.3%). HCV RNA positive individuals were genotyped: genotype 3a (45.5%) was dominant among the other detected genotypes, followed by 1a (11.4%), 3b (4.9%), and 2a (4.1%). It was concluded that the highest prevalence of HCV was found in females, and that the dominant genotype of the screened individuals was 3a genotype.